Histone deacetylase inhibitors induce epithelial-to-mesenchymal transition in prostate cancer cells. - Dejuan Kong; Aamir Ahmad; Bin Bao; Yiwei Li; Sanjeev Banerjee; Fazlul H Sarkar (PLoS ONE, 2012)
Clinical experience of histone deacetylase inhibitors (HDACIs) in patients with solid tumors has been disappointing; however, the molecular mechanism of treatment failure is not known. Therefore, we sought to investigate the molecular mechanism of treatment failure of HDACIs in the present study. We found that HDACIs Trichostatin A (TSA) and Suberoylanilide hydroxamic acid (SAHA) could induce epithelial-to-mesenchymal transition (EMT) phenotype in prostate cancer (PCa) cells, which was associated with changes in cellular morphology consistent with increased expression of transcription factors ZEB1, ZEB2 and Slug, and mesenchymal markers such as vimentin, N-cadherin and Fibronectin. CHIP assay showed acetylation of histone 3 on proximal promoters of selected genes, which was in part responsible for increased expression of EMT markers. Moreover, TSA treatment led to further increase in the expression of Sox2 and Nanog in PCa cells with EMT phenotype, which was associated with cancer stem-like cell (CSLC) characteristics consistent with increased cell motility. Our results suggest that HDACIs alone would lead to tumor aggressiveness, and thus strategies for reverting EMT-phenotype to mesenchymal-to-epithelial transition (MET) phenotype or the reversal of CSLC characteristics prior to the use of HDACIs would be beneficial to realize the value of HDACIs for the treatment of solid tumors especially PCa.